The readiness and challenges in the Industrialised Building System (IBS) adoption in Sarawak from G7 contractors’ perspective/ Muhammad Syafiq Bahrin Samsi ... [et al.] - Samsi, Muhammad Syafiq Bahrin; Zainuddin, Mohd Firdaus; Yop Zain, Fairiz Miza; Saidin, Mohamad Tajudin; Mamat, Mohd Esham; Zainal Abidin, Zaiwanizar (Universiti Teknologi MARA, Perak, 2024)
Industrialised Building System (IBS) is defined as method for thorough integration of subsystems, components, and parts into a single overall system that utilizes industrialised manufacturing, transportation, assembling, and erection on site. Buildings that are built by using IBS method have many benefits, including high quality, low cost, fast construction, high flexibility, minimal wastage, and less environmental impact. However, adopting IBS in Sarawak has several hindrances such as logistical situation in rural Sarawak and the overpriced IBS adoption due to lack of manufacturer in the areas which causes lack of readiness among contractors. Thus, the aim of this research is to identify the G7 contractors’ readiness and investigate the challenges of IBS adoption for construction in Sarawak. One hundred and twenty-five sets of questionnaire surveys were distributed to G7 contractors in Kuching area by using google form as online medium and were analysed using SPSS version 26 software. The findings from the survey showed that Sarawak G7 contractors still lack readiness in IBS adoption due to challenges faced. Thus, further research needed on steps to be taken to reduce challenges in adopting IBS in Sarawak.